VERTICAL PROGRESSION AND SPREAD OF PHYTOPHTHORA LEAF INFECTION IN BLACK PEPPER IN ARECA-BLACK PEPPER MIXED CROPPING SYSTEM - AND M. ANANDARAJ, N. RAMACHANDRAN, Y. R. SARMA (Indian Phytopathology, 2002)
Vertical progression and lateral spread of foliar infections caused by ’Phytophthora palmiuora’ MF. in black pepper, Piper nigrum L., uisÂ·aÂ·uis the role of rain splash were studied in a pepper garden mix-cropped with arecanut (Areca catechu L.). Infections first appeared on the tender leaves and terminal portions of runner shoots creeping on the ground indicating that soil was the primary source of inoculum. The infection gradually spreads upwards in a step-wise manner and also across the adjacent vines. In a few vines, the infection was recorded even at heights over 9 m. The splash water collected at 1,2 and 3 m away from the infected vines and at heights of 0, 0.5 and 1 m contained ’P paimiuora’ MF." (P. capsici). This confirmed the spread of the pathogen through rain splashes.